Functional Cell-Based Assays in Microliter Volumes for Ultra-High Throughput Screening - Wunder, Frank; Kalthof, Bernd; Muller, Thomas; Huser, Jorg (Combinatorial Chemistry & High Throughput Screening, 2008)
Functional cell-based assays have gained increasing importance for microplate-based high throughput screening (HTS). The use of high-density microplates, most prominently 1536-well plates, and miniaturized assay formats allow screening of comprehensive compound collections with more than 1 million compounds at ultra-high throughput, i.e. in excess of 100,000 samples per day. uHTS operations with numerous campaigns per year should generally support this throughput at all different steps of the process, including the underlying compound logistics, the (automated) testing of the corporate compound collection in the bioassay, and the subsequent follow-up studies for hit confirmation and characterization. A growing number of reports document the general feasibility of cell-based uHTS in microliter volumes. In addition, full automation with integrated robotic systems allows the realization of also complex assay protocols with multiple liquid handling and signal detection steps. For this review, cell-based assays are categorized based on the kinetics of the cellular response to be quantified in the test and the readout method employed. Thus, assays measuring fast cellular responses with high temporal resolution, e.g., receptor mediated calcium signals or changes in membrane potential, are at one end of this spectrum, while tests quantifying cellular transcriptional responses mark the opposite end. Trends for cell-based uHTS assays developed at Bayer-Schering Pharma are, first, to incorporate assay integral reference signals allowing the experimental differentiation of target hits from non-specifically acting compounds, and second, to make use of kinetic, real-time readouts providing additional information on the mode-of-action of test compounds.
Keywords: Ultra-High Throughput Screening